Micromechanical and numerical analysis of packing and size effects in elastic particulate composites. (1st September 2017) - Majewski, M.; Kursa, M.; Holobut, P.; Kowalczyk-Gajewska, K.
Abstract: Effects of particle packing and size on the overall elastic properties of particulate random composites are analyzed. In order to account for the two effects the mean-field Morphologically Representative Pattern (MRP) approach is employed and an additional interphase surrounding inclusions (coating) is introduced. The analytical mean-field estimates are compared with the results of computational homogenization performed using the finite element (FE) method. Periodic unit cells with cubic crystal-type arrangements and representative volume elements with random distributions of particles are used for verification purposes. The validity of the MRP estimates with respect to the FE results is assessed.